APOE4 and doxorubicin impair inhibitory interneuron function and homeostatic regulation in the entorhinal cortex - Nancy Luo; Harshul Pandit; Shreya Kalra; Erin Tran; Jeanne Mandelblatt; Stefano Vicini; G. William Rebeck (PLoS ONE, 2026)
APOE4 is a risk factor for several disease states associated with cognitive impairment, including Alzheimer’s disease and cancer-chemotherapy induced cognitive impairment. Using mouse knock-in models of human APOE alleles, we examined the effects of APOE genotype and chemotherapy on the ex vivo electrophysiological characteristics of excitatory and inhibitory neurons in the entorhinal cortex (EC). We found that APOE4 is associated with a significantly higher excitatory/inhibitory ratio (0.33 ± 0.04) in the layer 2/3 pyramidal cells of the entorhinal cortex compared to APOE3 (0.19 ± 0.04). We crossed APOE mice to mice with parvalbumin (PV) interneurons tagged with tdTomato, allowing us to measure effects specifically on this inhibitory cell type. For EC pyramidal neurons, the chemotherapeutic agent doxorubicin caused increases in the amplitudes of both spontaneous excitatory and inhibitory post-synaptic currents, with significant responses (***p < 0.001; **p < 0.01 respectively) in APOE3 brains. For EC PV neurons, APOE4 genotype was associated with significantly lower firing rates at injections of high currents (**p < 0.01), but rates were unaffected by doxorubicin. Doxorubicin doubled the percentage of PV cells that showed inactivation block in APOE3 brains (25% to 52%) but had no effect on APOE4 brains (50% to 54%). This ex vivo study suggests that APOE4 impairs homeostatic synaptic transmission in pyramidal cells under control conditions and causes a lack of responsiveness to a stressor (doxorubicin treatment) in PV cells.